Clinical and morphological aspects of the development of secondary ophthalmic hypertension in uveal melanoma - E. E. Grishina; G. R. Setdikova; I. D. Kim; A. M. Bogatyrev; I. A. Loskutov; E. R. Eremeeva (Российский офтальмологический журнал, 2022)
Ophthalmic hypertension is mostly associated with medium- or large-sized melanomas. The pathogenesis of persistent IOP elevation in uveal melanoma is not fully understood at present.   Purpose. To analyze the clinical and morphological mechanisms of the development of secondary ophthalmic hypertension in patients with uveal melanoma.   Material and methods. The case histories of 26 patients with T3N0M0-T4N0M0 uveal melanoma were analyzed retrospectively from 2015 to 2019. The main group included 18 patients with secondary monolateral IOP elevation while the control group was composed of 8 patients with normal IOP. Tumors in both groups were comparable in size. All patients underwent eradication treatment (enucleation/exenteration). Enucleated eys were histologically examined.   Results. Pronounced pathological changes of the iridocorneal angle, iris and ciliary body were found morphologically in all specimens with elevated IOP. The following dominating mechanisms ofophthalmic hypertension were detected: iris and anterior chamber angle neovascularization; tumor-associated chronic uveitis; obstruction of trabecular meshwork by cellular elements (pigment-rich macrophages, blood cells, inflammatory cells); fibrosis and deformation of trabecular meshwork and Schlemm's canal; closed angle glaucoma with lens-iris diaphragm shift; tumor invasion into the angle.   Conclusions. Investigation of morphological changes in patients with UM and found resemblances with already studied non-tumor forms of glaucoma may help find previously undetectable receptors for the development of targeted anti-tumor drugs.